Chegou a nossa hora Brasil! A influência político/religiosa do movimento “The Send” na juventude evangélica brasileira - Ferreira, Eli Couto (2022)
This dissertation proposes to analyze the movement named The Send, which seeks to influence Brazilian evangelical youth through a theme of missionary awakening and social transformation. The movement was born in the USA and militates in the field of religion, but not limited to it, they call on the youth to “dominate” all spaces on civil society. The group of young Brazilian evangelicals linked to the movement has a diverse profile, which reproduces the heterogeneity that characterizes this group. Therefore, we propose in this dissertation an analysis of the political/religious influence that The Send movement have on a portion of Brazilian evangelical youth that we identify here as fundamentalist. The problem to be discussed refers to the political use of the religious discourse present in The Send movement, which seeks to mobilize a portion of Brazilian evangelical youth around a neoliberal fundamentalist political project. Through research/bibliographic research, we seek to understand the movement from its formation to the construction of the discourse present in the events, as well as the desire of its components to exert political influence over young people. Our work indicates that the modus operandi of The Send is the same present in a significant portion of Brazilian evangelicals, who consume much of the "theological" content produced by the Americans, our research indicates that The Send is an adaptation of fundamentalism to young people.(AU)